(untitled) (Semiárida, 2020)
This work aimed to evaluate farmers’ profile at Ibirapuitã´s Envirnonmental Protected Area (EPA). The Ibirapuitã´s EPA covers the municipalities of Santana do Livramento, Alegrete, Rosário do Sul e Quaraí, RS, Brazil. Semi-structured interviews were conducted with non random samples -based in Agrarian Systems Diagnosis Analysis. Previously to the interviews a typology was created using data from relief, vegetation and soil use maps and historical documentation. Using data from these farmers´ interviews, 11 binary and 16 quantitative characteristics were selected from sampling units representing Ibirapuitã´s EPA. The relationships among these characteristics and farmers´ profiles were evaluated. Data were analyzed using the software MULTIV. The first profile could be called enterprise farmers, with larger areas, larger herds and more specialized production systems, that could be identified by higher investments in cultivated pastures or health facilities, such as pumping water at home. In the second one, called the “familial beef cattle breeders”, there were no contracted workers. This group owned smaller areas, higher stocking rates and a significant contribution of retirement salaries in their incomes. In this group, another subdivision could be found according to scholarship degree. This was indicated by a better access to information wich enhances a diversification of production for self-consumptio. It was also observed better practices in natural grasslands beef cattle raising systems. Farmers were grouped management according to the degree of cash flows and also to social and cultural characteristics influencing grassland management practices. This work demonstrate that social and cultural characteristics influences in natural grasslands management.